Perceived Control, Motivation, & Coping. - Skinner, Ellen A. (Sage series on individual differences and development., 1995)
At every point in the lifespan, individual differences in a sense of control are strong predictors of motivation, coping and success and failure in a wide range of domains. What are the origins of these individual differences, how do they develop and what are the mechanisms by which they exert such an influence on psychological functioning? To answer these questions, this book draws on theories and research covering key control constructs, including self-efficacy, learned helplessness, locus of control and attribution theory. Skinner also considers such issues as: the origins of control.